Building a Business Model for Micro, Small and Medium Enterprises (MSME) after the Covid-19 Pandemic (Case Study of MSME Fried Onions UMI 4 R Kitchen) - Nurlinda Nurlinda; Vivianti Novita; Dina Arfianti Siregar; Zulia Hanum; Nirmadarningsih Hiya (International Journal Reglement & Society (IJRS), 2023)
This research provides an overview of Micro, Small and Medium Enterprises (MSMEs) that will build and are starting a business, so they can obtain simple information to design a business model according to the intended market segment. The purpose of the business planning model canvas is to get information about the best planning for a business if it is applied as an appropriate technology and model in MSMEs. The long-term goal of this research is to provide literacy to MSMEs on how to develop a business model concept that is that is easy, simple and complete. This research will also contribute to new and pioneering MSME actors in designing business models before building a business. This will help MSMEs in mapping each business segment, so that potential risks can be found early on and the solutions needed. The long-term business model design will serve as a guide and help MSMEs survive crisis such the COVID-19 Pandemic, so that they are not shaken immediately when the crisis comes. This research is a qualitative research. Data collection techniques were carried out using a combination of interviews and Group Discussion Forums. Data analysis used descriptive analysis and BMC matrix. The results of the study that BMC for fried onion MSMEs UMI 4R Kitchen can be concluded that of the nine BMC elements, there are six elements that must be improved, namely Customer Segment elements, Channel Elements, Value Propositions Elements, Key resources elements, Key partners elements; and cost structure elements.